Imported intermediates, technology spillover, and green development: Evidence from Chinese firms - Huang, Yingfei; Pei, Jiansuo (Frontiers in Environmental Science, 2022)
Firms are critical stakeholders to achieve sustainable development. Thus, corporate environmental performance is a subject of broad concern. In an era of globalization, the relationship between trade and environment is hotly debated. One of the central questions is that, will imported intermediates contribute to pollution abatement? Using Chinese firm-level data from 2000 to 2013, the paper measures the technology spillover of imported intermediates, and empirically tests the inhibitory effect and influence mechanism on pollution intensity with fixed effects model and instrumental variables approach. We find that: (1) The technology spillover directly increases innovation, and indirectly affects innovation by importing diversity. Imported intermediates empower firms with insufficient innovation to control pollution. However, the incentive effect declines when innovation gradually improves. (2) The technology spillover diffuses along the industrial chain. Downstream firms benefit from the diffusion and thus have lower pollution intensity than upstream firms. (3) The technology spillover contributes to the end-of-pipe emission reduction. Also, it improves energy efficiency and promotes source governance. Further, the environmental benefits of imported intermediates differ along a number of dimensions including sourcing countries, firm ownership and location. Thus, we pinpoint a new channel concerning trade-induced technique effect. Meanwhile, our results confirm the rationale of liberalization and facilitation policies for imported intermediates. That is, trade policies have the potential to better contribute to sustainable development goals.